The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d2ra08244f
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethyl cellulose-based materials as an alternative source for sustainable electrochemical devices: a review

Abstract: This review describes the applications of CMC and superiority of other bio-based materials over the traditional costly and synthetic polymers in electrochemistry due to their abundance, versatility, sustainability and low cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 162 publications
0
4
0
Order By: Relevance
“…[33] Natural polymer electrolytes are the preferred choice over their synthetic counterparts due to their cost-effectiveness, biocompatibility, and widespread availability. [34,35] It's noteworthy to use cellulose and its derivatives in the construction of natural polymer electrolytes because they are non-toxic and non-harmful, unlike materials that are inherently toxic and harmful. [36] Jiang et al previously reported the utilization of viologen/cellulose-based electrochromic devices, employing a strategy similar to the one delineated in this study.…”
Section: Methodsmentioning
confidence: 99%
“…[33] Natural polymer electrolytes are the preferred choice over their synthetic counterparts due to their cost-effectiveness, biocompatibility, and widespread availability. [34,35] It's noteworthy to use cellulose and its derivatives in the construction of natural polymer electrolytes because they are non-toxic and non-harmful, unlike materials that are inherently toxic and harmful. [36] Jiang et al previously reported the utilization of viologen/cellulose-based electrochromic devices, employing a strategy similar to the one delineated in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, CMC is considered an alternative candidate for PVDF binders because of its solubility in water. In general, CMC is used in the sodium salt form [63][64][65]. Figure 1(b) shows the chemical structure of CMC, which contains carboxymethyl and hydroxyl groups.…”
Section: Role Of Binder In Libsmentioning
confidence: 99%
“…The combo of ethyl cellulose and activated carbon serves as a good candidate for green electronics applications. Important to note that, several review themes corresponding to cellulose-based derivatives are hugely available and reported recently [82,83].…”
Section: Cellulose Acetate-based Electrolytesmentioning
confidence: 99%